2015
DOI: 10.1039/c5ra15463d
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dot grafted SrAl2O4:Eu,Dy dual-emitting phosphor for ratiometric temperature sensing

Abstract: We incorporated carbon dots (CDs) into a SrAl2O4:Eu,Dy phosphor (SAO), and made use of the dual emission from the CDs and SAO within such a composite to realize ratiometric temperature sensing from 100 to 400 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…When light irradiation stops, empty hole is motivated again and is released to the valence band. The hole migrates to the Eu + and is captured and that results in producing fluorescence again, which is an important reason why light-emitting materials afterglow time lasts long 15, 17, 18 .
Figure 2( a ) Hydrogel luminescence mechanism. ( b ) The excitation spectrum of hydrogel at 513 nm emission wavelength; interleaved patterns show the photographs of hydrogel: the sample with yellowish white color before the excitation treatment of sunlight (the left one), the sample with strong green color after the excitation treatment of sunlight (the right one).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When light irradiation stops, empty hole is motivated again and is released to the valence band. The hole migrates to the Eu + and is captured and that results in producing fluorescence again, which is an important reason why light-emitting materials afterglow time lasts long 15, 17, 18 .
Figure 2( a ) Hydrogel luminescence mechanism. ( b ) The excitation spectrum of hydrogel at 513 nm emission wavelength; interleaved patterns show the photographs of hydrogel: the sample with yellowish white color before the excitation treatment of sunlight (the left one), the sample with strong green color after the excitation treatment of sunlight (the right one).
…”
Section: Resultsmentioning
confidence: 99%
“…One of the representative fluorescent materials is synthesized by rare-earth, which has excellent fluorescent property 1315 . In the past years, rare-earth fluorescent material was studied primarily on Eu 2+ /Dy 3+ doped SrAl 2 O 4 for the merits of environment-harmless and strong green fluorescence 16, 17 . It was reported that phosphorescent Eu 2+ /Dy 3+ doped SrAl 2 O 4 was successfully synthesized and used as temperature measurement 18 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods for measuring the temperature, fluorescence‐based temperature measurements have attracted much attention because of the merits of being non‐invasive, giving a fast response, and being robust even under strong electromagnetic fields . Fluorescence‐based measurements using luminescent materials activated with semiconductor nanocrystals, carbon dots, or rare‐earth ions are commonly based on the decrease in the emission intensity with increasing temperature by the thermal activation of non‐radiative deactivation pathways . Compared to single‐intensity‐based measurements, fluorescence ratiometric methods are more robust and convenient for actual applications.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] By measuring the uorescence intensity ratio of the thermal coupling energy levels of the RE doped materials, the temperature changes around the uorescent probe can be monitored. [24][25][26][27][28][29][30][31] Therefore, RE ion doped temperature sensing materials are considered to be a very promising for temperature detection materials. [32][33][34][35][36][37][38][39][40] Among the trivalent RE ions, Ho 3+ has plentiful energy levels and obvious luminescence characteristics in the visible light region, 41,42 and it has the ability to obtain intense optical light by the sensitization of other RE ions.…”
Section: Introductionmentioning
confidence: 99%